Pengolahan Limbah Tekstil dengan Metode Hibrid Menggunakan Sistem Filtrasi Bottom Ash dan Constructed Wetland - Pieter Jhon Joshua Daris; Haryati Bawole Sutanto; Guruh Prihatmo (Universitas Katolik Musi Charitas, 2020)
Textile wastewater that is discharged directly can cause damage to aquatic ecosystems and affects human health, thus requiring an effective alternative wastewater treatment. This research was conducted using a hybrid method that aims to eliminate pollutants in textile waste. The study was conducted by flowing textile waste into the bottom ash filtration and proceed to constructed wetland system with the residence time of 4 days. The results showed a decrease in the value of TDS, TSS, COD, and chromium by 16.47%, 97.09%, 72.14%, and 94.78% respectively in bottom ash output; and 13.12%; 57.53%; 7.52%; and 0.35% in the constructed wetland output. Therefore, the use of the hybrid method has been effective in treating textile waste by looking at the decrease in each test parameter.